Calcium from Pacific White Shrimp (Litopeneaus vannamei) Shells: Properties and Function as Fortificant in Soy Milk - Dechapinan, Saranya; Judprasong, Kunchit; On-nom, Nattira; Tangsuphoom, Nattapol (Food and Applied Bioscience Journal, 2017)
Shrimp shells are the waste from shrimp processing industry that can be a potential source of calcium. This study aimed to determine the chemical and functional properties of calcium gluconate (SCG) and calcium lactate (SCL) prepared from shrimp shells and their application as food fortificants in soy milk. Calcium extraction was performed at 70°C for 2 h by mixing the enzymatically-deproteinized shrimp shell with the solutions of gluconic or lactic acid containing equivalent number dissociated carboxyl group to calcium available in the shells. The obtained calcium salts were characterized using Fourier-transformed infrared spectroscopy. Both gluconic and lactic acids gave >80% calcium extraction yield. The obtained SCG and SCL had calcium solubility of >70% across the pH range of 3–8. Dialyzability of SCG and SCL, evaluated by in vitro equilibrium, and continuous flow dialysis methods, was 30–40% and 60–70%, respectively. Soy milks fortified with SCG and SCL to obtain a final calcium concentration of 125 mg/100 mL had slightly different color and slightly higher apparent viscosity than the unfortified one. However, such differences did not affect the sensory acceptability scores of the product in all attributes. Although the solubility and dialyzability of SCG and SCL were lowered by the presence of food matrix of soy milk, the prepared calcium salts could still increase total calcium and dialyzable calcium contents of the fortified samples. Therefore, Pacific white shrimp shells can be used to prepare different formsof calcium salts with potential application as fortificants in food.